Penatalaksanaan Fisioterapi pada Kasus Carpal Tunnel Syndrome Dextra dengan Modalitas Ultrasound dan Carpal Bone Mobilization - Dhea Vizalita Rizaldo; Putra Hadi; Indah Permata Sari (Prosiding Seminar Kesehatan Nasional, 2022)
Carpal tunnel syndrome is a symptomatic compression neuropathy of the median nerve at the wrist in the form of increased pressure in the wrist and decreased nerve function at that level. Symptoms range from pain and paresthesias to muscle atrophy. This study aims to determine the management of physiotherapy in carpal tunnel syndrome by using ultrasound modalities and carpal bone mobilization in reducing pain and increasing joint range of motion. The method used is a study method with one respondent, conducted in April 2022 with therapy twice a week for three weeks. The measuring instrument used in this case study is pain with VAS and joint range of motion with a goniometer. The result is that after being given six treatments, it was found that there was a reduction in pain and an increase in the range of motion of the joints. The conclusion of this study is that ultrasound and carpal bone mobilization can reduce pain and increase joint range of motion.